Peran Moderasi Etika Kerja Islami pada Kreativitas terhadap Kinerja Usaha Pelaku UMK di Kabupaten Wajo - Mahendra, Yusril; Misbach, Irwan; Syaharuddin, Syaharuddin (Universitas Batanghari Jambi, 2025)
This study aims to examine the influence of creativity on business performance carried out by MSE actors in Wajo Regency. This is also done to test the effect of the application of Islamic work ethics in strengthening MSE actors to be more creative in improving their performance. This study uses an explanatory research design. Data collection was carried out using the field survey method. The sampling technique used purposive sampling with a sample of 244 MSE actors spread across 14 sub-districts in Wajo Regency. The sample in this study is business owners. This study also uses an analysis method in hypothesis testing, namely Partial Last Square (PLS). The results of this study show that creativity has a positive and significant effect on the business performance of MSE actors in Wajo Regency. Islamic work ethics does not have a strengthening effect on MSE actors to be more creative in improving their performance.